Pengaruh modifikasi pola hidup dengan atau tanpa metformin terhadap kadar C-reactive protein pada penderita obesitas - Muhammad Budiman; Mardianto dr; Dharma Lindarto (Majalah Kedokteran Nusantara The Journal Of Medical School, 2012)
Background : Obesity is a multifactorial disease caused by accumulation of excessive adipose tissue that can cause metabolic syndrome and increase cardiovascular event. Adipose tissue secretes adipokine that induces the formation of CRP. Metformin as an antidiabetic agent has anti inflammatory effect.Aim of the study : Find out whether combination of medical life style and metformin in obesity subjects can improve CRP level. Method : This study was a clinical trial held for 12 weeks on obesity subjects which divided in to two groups. Group was subjects with medical life style without metformin and group was subjects with combinationof medical life style and metformin. Results : After 12 weeks of intervention in group without metformin (n= 19) there was significant improvement in body weight 78.01 (SD 11.33) compared to 75.68 (SD 11.02), P= 0.0001); waist circumference 95.47 (SD 7.12) compared to 90.07 (SD 7.63), P = 0.001; body mass index 32.35 (SD 4.13) compared to 31.26 (SD 4.15), P = 0.0001; and hs-CRP 3.03 (SD 2.20) compared to 3.22 (SD 2.40), P = 0.445. While metformin group (n= 19) the body weight was 76.07 (SD 13.06) compared to 72.33 (SD 12.97), P = 0.0001; waist circumference 93.97 (SD 9.70) compared to 87.80 (SD 9.42), P = 0.0001; body mass index 32.49 (SD 4.88) compared to 30.70 (SD 4.72), P= 0.0001; and hs-CRP 3.02 (SD 2.25) compared to 2.63 (SD 1.93), P = 0.292. There was significant difference in body weight and body mass index.Conclusion : Implementation of medical life style in 12 weeks improved spesific antropometric parameter and metformin complementation did not improve the CRP level significantly in obesity subjects.Keywords : obesity; lifestyle; modification; metformin; CRPBackground : Obesity is a multifactorial disease caused by accumulation of excessive adipose tissue that can cause metabolic syndrome and increase cardiovascular event. Adipose tissue secretes adipokine that induces the formation of CRP. Metformin as an antidiabetic agent has anti inflammatory effect.Aim of the study : Find out whether combination of medical life style and metformin in obesity subjects can improve CRP level. Method : This study was a clinical trial held for 12 weeks on obesity subjects which divided in to two groups. Group was subjects with medical life style without metformin and group was subjects with combinationof medical life style and metformin. Results : After 12 weeks of intervention in group without metformin (n= 19) there was significant improvement in body weight 78.01 (SD 11.33) compared to 75.68 (SD 11.02), P= 0.0001); waist circumference 95.47 (SD 7.12) compared to 90.07 (SD 7.63), P = 0.001; body mass index 32.35 (SD 4.13) compared to 31.26 (SD 4.15), P = 0.0001; and hs-CRP 3.03 (SD 2.20) compared to 3.22 (SD 2.40), P = 0.445. While metformin group (n= 19) the body weight was 76.07 (SD 13.06) compared to 72.33 (SD 12.97), P = 0.0001; waist circumference 93.97 (SD 9.70) compared to 87.80 (SD 9.42), P = 0.0001; body mass index 32.49 (SD 4.88) compared to 30.70 (SD 4.72), P= 0.0001; and hs-CRP 3.02 (SD 2.25) compared to 2.63 (SD 1.93), P = 0.292. There was significant difference in body weight and body mass index.Conclusion : Implementation of medical life style in 12 weeks improved spesific antropometric parameter and metformin complementation did not improve the CRP level significantly in obesity subjects.Keywords : obesity; lifestyle; modification; metformin; CRP